Analysis of technological factors that significantly affect the formation of stresses in the cast machine parts - Акимов, Олег Викторович; Алёхин, Виталий Игоревич; Пензев, Павел Сергеевич; Дяченко, Алла Вячеславовна; Овчаренко, Анастасия Михайловна (Eastern-European Journal of Enterprise Technologies, 2015)
The results of shrinkage porosity distribution in cast parts of the block-crankcase of the internal combustion engine (ICE) were presented. It was shown that the localization of gas-shrinkage porosity coincides with the localization of residual stresses in a body of cast block-crankcase of ICE. Technological factors that significantly affect the formation of residual stresses were identified. These include the selected inoculant type and alloy inoculation modes; design of the gating system and rods, heat treatment modes. The measures that reduce residual stresses, in particular, a rational choice of the alloy; modifiers having an optimal combination of alloying and graphitizing elements; reduction of shrinkage inhibition during solidification, ensured by the rational design of rods; developing the gating system for the optimal flow of hydro- and gas-dynamic processes during the mould filling with the melt were proposed.